ANALYSIS OF THE QUALITY OF SMOKED WHITELIPPED EEL CATFISH IN â€œMINA MULYAâ€ FISH PROCESSING GROUP, PASIR SAKTI, EASTERN DISTRIC OF LAMPUNG - Mrdiana, Novita (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
The aimof this researchwas to find out the quality of smoked whitelipped eel catfish in difference smoking time at â€œMinaMulyaâ€ Fish Processing Group, Pulosari Village, Pasir Sakti, Eastern Distric of Lampung. The reaserch was conducted infour levels smoking time,which are 1, 2, 3 and 4 hours. The analysis on smokedwhitelipped eel catfish applied kind of proximate analysis (fat level, protein level,ash level and moisture level), microbiology analysis (Total Plate Count (TPC), Escherechia coli bacteria, Salmonella sp. bacteria and Staphylococcus aureus bacteria) and organoleptic analysis (appearance, odour, flavour and texture). The results of this research show that the smoking time levels affect the quality of whitelipped eel catfish. The proximate analysis result show differences among the treatments especially on the proximate analysis. Organoleptic analysis shows that on appearance parameter, only whitelipped eel catfish that are smoked for 3 hours fulfill theminimumvalue (7,0). Whereas organoleptic values for odour, flavour and texture parameter showthat onlywhitelipped eel catfish that are smoked for 1 hour that does not fulfill theminimum value. Microbiology analysis shows that the content of TPC and Escherechia coli bacteria smoked fish get under the maximum value of tolerance arrenged on SNI in each treatment. The content of Salmonella sp. and Staphyococcus aureus bacteria are negative on the whole treatments.